Burke, The Renaissance - Morrow, S. Rex (Teaching History: A Journal of Methods, 1998)
Peter Burke, a Fellow at Emmanuel College, University of Cambridge, has written an effective yet concise overview of the rise and fall of the Italian Renaissance. The text, which is only 77 pages, consists of five chapters: The Myth of the Renaissance; Italy: Revival and Innovation; The Renaissance Abroad; The Disintegration of the Renaissance; and Conclusion. The text closes with a comprehensive bibliography that is divided into fifteen significant subsections for the reader’s benefit.